2017
DOI: 10.1093/hmg/ddx423
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention rescues myopathy associated with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder with complex symptomology. In addition to a predisposition to tumors, children with NF1 can present with reduced muscle mass, global muscle weakness, and impaired motor skills, which can have a significant impact on quality of life. Genetic mouse models have shown a lipid storage disease phenotype may underlie muscle weakness in NF1. Herein we confirm that biopsy specimens from six individuals with NF1 similarly manifest features of a lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…In parallel we observed a fiber type shift from glycolytic type 2 fibers to oxidative type 2 and in part to type 1 fibers. In adult Nf1 Prx1 mice, no fiber type shift was reported [18], however this had not been quantified. During embryonic and fetal myogenesis, muscle fibers predominantly show oxidative-type gene and protein expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In parallel we observed a fiber type shift from glycolytic type 2 fibers to oxidative type 2 and in part to type 1 fibers. In adult Nf1 Prx1 mice, no fiber type shift was reported [18], however this had not been quantified. During embryonic and fetal myogenesis, muscle fibers predominantly show oxidative-type gene and protein expression.…”
Section: Discussionmentioning
confidence: 97%
“…Inactivation of Nf1 in limb mesenchyme during development using Prx1 Cre recapitulated the skeletal manifestations of NF1 [15,16], but also caused an early-onset defect in embryonal myogenesis [17], providing the first evidence for a direct involvement of Nf1 in myogenesis. Postnatally, Nf1 Prx1 mice recapitulated Nf1 features as muscle weakness and fibro-fatty infiltration of muscle [17,18]. However, in this model, Nf1…”
Section: Introductionmentioning
confidence: 83%
“…These novel findings led us to speculate that NF1 may have a key role in the regulation of muscle lipid metabolism. More recently, Summers et al published a report examining the IMCL found in Nf1 MyoD -/muscle [6]. Lipidomics identified an increase in triglycerides, diglycerides, and cholesterol esters containing long-chain fatty acids (LCFAs).…”
Section: Introductionmentioning
confidence: 99%
“…L-carnitine has previously been shown to treat muscle weakness in patients with other metabolic myopathies [7][8][9]. However, the mouse chow containing 70% octanoic acid as a MCFA source [6] is an approach that is not directly translational to dietary modification in humans. Moreover, it was unknown whether L-carnitine supplementation alone would be sufficient to produce significant reductions in muscle lipid and improvements in strength; an intervention that could be more readily adopted than changes in dietary fat intake.…”
Section: Introductionmentioning
confidence: 99%
“…Intramyocellular lipid deposits have been found in both NF1 ‐deficient human and Nf1 ‐null mouse muscle, consistent with myopathy. Weakness and lipid buildup were rescued in a knockout mouse model with a medium‐chain fatty acid and carnitine‐enriched diet (Summers et al, ), suggesting a potential therapy for patients.…”
Section: Meeting Sessionsmentioning
confidence: 99%